Jewish travel in antiquity - Hezser, Catherine, 1960- (Texte und Studien zum antiken Judentum, 2011)
HauptbeschreibungThis book provides the first comprehensive study of Jewish travel and mobility in Hellenistic and Roman times, based on a critical analysis of Jewish, Graeco-Roman, and early Christian literary, epigraphic, and archaeological sources and a social-historical evaluation of the material. Catherine Hezser shows that certain segments of ancient Jewish society were quite mobile. Mobility seems to have increased in the later Roman period, when an extensive road system facilitated travel within the province of Syria-Palestine and the neighbouring Middle Eastern regions. Second Temple.